Community-Based Learning Activities on the Local History of Following the trail Mahasanook Swamp to Awaken Sawhan Swamp to Strengthen the Youth of Historical Communication for High School Students in Udon Thani. - Joynusnag, Chonlathee; Soithong, Parinya (Journal of Buddhist Education and Research (JBER), 2025)
The purposes of this research were 1) to study current state local history learning arrangements of high school students in Udon Thani Province and 2) to create community-based learning management activities. To strengthen the youth of historical communication for high school students in Udon Thani Province. This qualitative research methodology by data were collected from the Sawhan Swamp archaeological site area, located in Chiang Phin Subdistrict, Mueang Udon Thani District, Udon Thani Province. The information was assemble through in-depth interviews with 9 community leaders and 6 history teachers. The research instruments included in-depth interview guidelines, and the information were analyzed using inductive content analysis combined with the Triangulation Method. The research findings revealed that students lacked knowledge and interest in local history. Most schools did not have a clear curriculum or instructional materials for teaching local history, and teachers placed insufficient emphasis on this subject. To address these issues, the researcher developed a set of learning activities entitled “Following the trail Mahasanook Swamp to awaken Sawhan Swamp” using the community as the foundation for learning. This approach provided students with direct learning experiences and stimulate active learning, The students participated in planning, implementation and communication of historical content by themselves. Teacher was responsible for designing the learning stations and facilitating a supportive environment for the activities. The activities contributed to the development of students’ learning competencies and promoted more favorable attitudes toward local history. The findings align with the Ministry of Education’s focus and policies on managing the core history curriculum outlined in the 2022 Basic Education Core Curriculum, which emphasizes fostering pride in the intellectual heritage of ancestors, preserving and developing it, and applying it meaningfully in contemporary society.